The Relationship Between Magmatism and Deformation Along the Intra‐arc Strike‐Slip Atacama Fault System, Northern Chile. Issue 3 (3rd March 2020) - Seymour, N. M.; Singleton, J. S.; Mavor, S. P.; Gomila, R.; Stockli, D. F.; Heuser, G.; Arancibia, G.
Abstract: Magmatic arcs may play a major role in the initiation, behavior, and abandonment of intra‐arc strike‐slip systems. Here we present zircon U‐Pb and (U‐Th)/He geochronology/thermochronology with new mapping to relate Coastal Cordillera arc magmatism to sinistral shear along the Atacama fault system (AFS) in northern Chile. New dates from 18 intrusions along the AFS between 24.6°S and 27°S compiled with published data record a minor Early Jurassic magmatic pulse (195–175 Ma), broad latest Jurassic to Early Cretaceous (150–120 Ma) pulse, and a minor younger (120–105 Ma) pulse. Mylonitization occurred only along the margins of Early Cretaceous plutons and surrounding Paleozoic metasedimentary rock, whereas Jurassic plutons and metasedimentary rocks away from Early Cretaceous plutons lack mylonitic fabrics. Early Cretaceous magmatism facilitated AFS deformation by thermally weakening the crust with elevated geothermal gradients that enabled mylonitization to take place at ~5‐ to 7‐km depths and low stresses. Spatial variability of pluton emplacement produced significant rheological heterogeneity, giving rise to a highly segmented fault system that did not originate as a regional‐scale shear zone. Synkinematic dikes (~120–117 Ma) cut mylonitic fabrics, and a postkinematic dike (~110 Ma) records the end stages of slip. The cessation of slip coincided with cooling below ~180 °C at ~116–99 Ma as arc magmatism migrated eastward and geothermal gradients relaxed, coeval with a major reorganization in plate motion and the onset of seafloor spreading in the south Atlantic. Key Points: Early Cretaceous plutons are spatially and temporally associated with Atacama fault system deformation Thermal softening in and around heterogeneously distributed Early Cretaceous plutons facilitated local mylonitization by raising the brittle‐plastic transition to shallow crustal levels The end of slip on the AFS was coeval with the cessation of arc magmatism and widespread cooling